Comparison of Spectra of the Congenitally Deaf, Hard-of-Hearing and Voices of Well Hearing Persons - Škarić, Ivo (Array, 1998)
LTAS (long-term average spectrum) of the text read by 9 adult females out of which 5 were congenitally deaf and who had learnt to speak through specialized training and 4 hard-of-hearing, and by 12 adult males out of which 9 congenitally deaf and who also had learnt to speak and 3 hard of hearing were analyzed. The average LTAS of each of the four groups was compared with the average of 95 voices of hea-ring females and 95 males, respectively. It was found that an average F0 was markedly higher in persons with a hearing loss than in the he-aring ones, whereas their range of pitch was significantly less. The average LTAS of the deaf, of both males and females, was more similar to the one of the hearing subjects than to the severely hard-of-hearing subjects whose voices due to the sidetone effect was intensi-fied and consequently the range of the first formant and the range from 2-2.5 HZ was elevated. The similarity of the spectra between the congenitally deaf and the hearing subjects implies that hearing does not directly affect the formation of voice quality.